Knowledge, attitudes and practices of nurses and pharmacists towards adverse drug reaction reporting in the South African private hospital sector - Sophia Bogolubova; Neelaveni Padayachee; Natalie Schellack (AOSIS, 2018)
Background: Pharmacovigilance (PV) is an important tool in monitoring the quality, efficacy and safety of medicines, with spontaneous reporting being the mainstay system of reporting adverse drug reactions (ADRs) worldwide. ADRs are largely underreported in South Africa. Aim: This study aimed to evaluate the knowledge, attitudes and practices of pharmacists and nurses in the private hospital sector towards ADR reporting. Setting: This study was conducted in six private hospitals and clinics within a single hospital group in Johannesburg, South Africa. Method: A cross-sectional survey was conducted amongst healthcare professionals using a structured multiple-choice questionnaire containing 20 close-ended questions. Both electronic and paper questionnaires were used to obtain as many responses as possible. Results: A total of 233 healthcare professionals participated in the study. Of these, 78.5% were registered nurses and 21.5% were hospital pharmacists. Although three-quarters of participants believed ADR reporting to be important, most had received no previous PV training (76.2%) and did not know how to report an ADR (54.5%). The majority of participants (87.1%) believed that all ADRs should be reported, with 75.5% of participants believing they would report all ADRs they encountered in the future provided they had sufficient training and knowledge. The major factors discouraging participants from reporting was a lack of awareness with respect to the process of reporting as well as a lack of access to the ADR reporting form. Conclusion: The majority of participants require further training regarding ADR reporting. Although the knowledge of most participants was acceptable, the transition into practice needs to be improved.